2019
DOI: 10.1177/1751143719832169
|View full text |Cite
|
Sign up to set email alerts
|

Neurological determination of death in isolated brainstem lesions: A case report to highlight the issues involved

Abstract: The neurological determination of death in patients with isolated brainstem lesions or by disruption of the posterior cerebral circulation is uncommon and many intensivists may never see such a case in their career. It is also the only major difference between the “whole brain” and “brain stem” formulations for the neurological determination of death. We present a case of a patient with infarction of the structures supplied by the posterior cerebral circulation in whom death was diagnosed using neurological cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In total, 18 studies (15 with a single case, 1 with 2 cases, 1 with 4 cases, and 1 with 17 cases) reported the history (characteristics and/or evolution) of 38 patients with isolated brainstem death. 18,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Detailed descriptions of each case are provided in eTable 4 (links.lww.com/WNL/C424). All brain lesions were located primarily in the posterior fossa and of vascular etiology: 19 had an intraparenchymal hemorrhage (2 in the brainstem, 13 in the cerebellum, and 4 in both the brainstem and cerebellum), 14 had an ischemic infarct (1 in the cerebellum and 13 in both the brainstem and cerebellum), and 5 had a subarachnoid hemorrhage.…”
Section: Characteristicsmentioning
confidence: 99%
“…In total, 18 studies (15 with a single case, 1 with 2 cases, 1 with 4 cases, and 1 with 17 cases) reported the history (characteristics and/or evolution) of 38 patients with isolated brainstem death. 18,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Detailed descriptions of each case are provided in eTable 4 (links.lww.com/WNL/C424). All brain lesions were located primarily in the posterior fossa and of vascular etiology: 19 had an intraparenchymal hemorrhage (2 in the brainstem, 13 in the cerebellum, and 4 in both the brainstem and cerebellum), 14 had an ischemic infarct (1 in the cerebellum and 13 in both the brainstem and cerebellum), and 5 had a subarachnoid hemorrhage.…”
Section: Characteristicsmentioning
confidence: 99%
“…Given the number of intensivists practicing in the UK, many will undertake testing less than once a year, particularly those working outside neurosciences critical care units [30].…”
Section: The Diagnosis Of Death Using Neurological Criteriamentioning
confidence: 99%
“…However, pathophysiologically isolated brainstem death does not follow the rostral to caudal brain function loss, as mentioned earlier. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…However, pathophysiologically isolated brainstem death does not follow the rostral to caudal brain function loss, as mentioned earlier. 9,10 Although in theory the concept of BD could be thought of as straightforward, the diagnosis of BD can be very challenging. This is particularly true in critically ill patients who have been on mechanical life support.…”
Section: Introductionmentioning
confidence: 99%